Effects of dietary γ-aminobutyric acid supplementation on growth, feed intake, and intestinal health of the juvenile Chinese mitten crab (Eriocheir sinensis) fed with high plant protein diets - Longhui Liu; Xuming Lu; Kejing Huang; Guiyuan Li; Yurong Liu; Yuxi Yan; Erchao Li; Liqiao Chen; Xiaodan Wang (Aquaculture International, 2026)

The Narrow‐Clawed Crayfish Pontastacus leptodactylus : Biology, Culture Development, and Prospects for Sustainable Aquaculture - Ardavan Farhadi; Muzaffer Mustafa Harlıoğlu; Erchao Li (Reviews in Aquaculture, 2026)
Pontastacus leptodactylus is a freshwater crayfish native to the Ponto‐Caspian region, with a distribution across Eastern Europe and Western Asia. This review synthesizes current knowledge on the biology, culture development, and prospects for sustainable aquaculture of P. leptodactylus . Commercial exploitation of P. leptodactylus has a long history in Western Europe and the Ponto‐Caspian region and has relied primarily on capture fisheries. Türkiye served as the principal exporter to international markets until the 1985 outbreak of crayfish plague ( Aphanomyces astaci ), which precipitated widespread stock collapses. In contrast, aquaculture development remained limited for decades and has only recently gained momentum, particularly, in China. Following the first identification of P. leptodactylus in China in 2021, interest in its culture has increased, with pilot‐scale farming trials and localized hatchery activities reported across several provinces. However, production remains limited in scale, and these developments are best regarded as early‐stage or proof‐of‐concept initiatives rather than established commercial aquaculture. Accordingly, this review provides an integrated appraisal of culture practices, including broodstock management, artificial incubation, juvenile feeding, stocking strategies, grow‐out systems, and health and biosecurity protocols. It further synthesizes market dynamics, value‐chain development, and welfare considerations alongside performance benchmarks. Key constraints such as the lack of species‐specific feeds, limited tools for cannibalism mitigation, and the absence of selective breeding programs are identified as major barriers to sustainable scale‐up. This review offers a framework to guide future research, management decisions, and aquaculture development for the sustainable utilization of P. leptodactylus .

Role of hypoxia in the behaviour, physiology, immunity and response mechanisms of crustaceans: A review - Cheng Zheng; Qianqian Zhao; Erchao Li; Daxian Zhao; Shengming Sun (Reviews in Aquaculture, 2022)
Crustaceans are often exposed to hypoxic stress in intensive aquaculture systems. Such stress leads to physiological, behavioural and biochemical changes, which can cause various metabolic disorders or even death. Crustacean response mechanisms to hypoxia stress are known to be complex, with their regulation involving multiple genes. In this review, after briefly exploring some known causes of hypoxic stress in aquaculture systems, we discuss the physiological adaptation strategies used by crustaceans in response to hypoxia and summarise recent information regarding the effects of hypoxia on the behaviour, survival, antioxidant ability, metabolic processes and innate immunity of crustaceans. In addition, we give particular emphasis to the known molecular mechanisms underlying hypoxia related to the hypoxia‐inducible factor 1 (HIF‐1) signalling pathway, the adenosine 5′‐monophosphate‐activated protein kinase signalling (AMPK) pathway, and apoptosis. Practically, it is clear that multiple measures need to be taken to prevent and regulate the adverse effects of hypoxic stress in intensive aquaculture systems, including development of hypoxia‐resistant breeds and nutritional regulation techniques. Overall, this review provides a theoretical basis for understanding the molecular mechanisms underlying hypoxic stress in crustaceans, while making conceptual connections with data from related study areas in other species.

Physiological change and nutritional requirement of Pacific white shrimp Litopenaeus vannamei at low salinity - Erchao Li; Xiaodan Wang; Ke Chen; Chang Xu; Jian G. Qin; Liqiao Chen (Reviews in Aquaculture, 2017)
The Pacific white shrimp Litopenaeus vannamei is a euryhaline species with optimal salinity of 20–25 practical salinity unit (psu) for growth and survival, but has been cultured in inland water with salinity DHA and EPA from LNA at low ambient salinity, but further studies are needed to further confirm this finding. Future research should focus on the understanding of physiological mechanism and adaptation associated with salinity change and nutritional manipulation. The specific dietary requirements of essential fatty acids, essential amino acids, vitamins and minerals and the nutrition‐mediated immune response also warrant further study on shrimp at low salinity.

Distiller’s dried grains with solubles as an alternative protein source in diets of tilapia - Chhorn Lim; Erchao Li; Phillip H. Klesius (Reviews in Aquaculture, 2011)
Distiller’s dried grains with solubles (DDGS), a dried residue that remains after the fermentation of grain mash by selected yeasts and enzymes to produce ethanol and carbon dioxide, is currently readily available and less expensive than other conventional protein sources on a per unit protein basis. The nutrient content and nutritional value of DDGS varies with the source and quality of the grains, fermentation time and efficiency, the drying process and the quantity of distiller’s solubles added. In general, corn and wheat DDGS are deficient in lysine and methionine for tilapia, with lysine being the most limiting. Research evaluating the nutritional value of DDGS showed that 20–30% DDGS derived from corn or wheat can be included in tilapia diets without requiring lysine supplementation. With supplementation of lysine, DDGS at levels of 40% or higher can be used without affecting growth performance and feed utilization efficiency. Distiller’s dried grains with solubles also contain yeast, a rich source of beta glucan and nucleotides that have been reported to enhance immunity and disease resistance in fish. Corn DDGS, owing to its high oil content, is rich in linoleic acid and is an excellent source of energy and essential fatty acids for tilapia. High concentrations of xanthophylls present in corn DDGS may impart yellow pigment in fish flesh if included at high levels. Taking into consideration various factors affecting the nutritional value of diets and the quality of pellet and fish products, 15–20% DDGS appears to be optimum in the diets of tilapia.